Future translators’ concerns regarding professional competences: a corpus study. - Plaza-Lara, Cristina (Escuela de Idiomas de la Universidad de Antioquia, 2023)
When entering the job market, prospective translators face certain difficulties concerning professional know-how that they have to overcome in order to succeed in their career. For this reason, the aim of this article is to provide insights into the main concerns of future translators regarding professional competences. To understand these concerns, a corpus was created using the questions posted by future translators in a forum located on a very well-known translation site: Proz. com. A total of 125 posts were processed and thematically coded using the corpus manager Sketch Engine. The thematic codes were based on two multi-componential models of translator competence: pacte’s and emt Board’s models. Once the content was coded, qualitative content analysis was carried out in order to analyse the main concerns of translators-to-be in relation to professional competences. Results show that marketing, industry, and business knowledge are among the main causes of worry of prospective translators. Although the results are not generalisable, the conclusions drawn from this study provide translator trainers with a comprehensive view of what professional competences should be reinforced in the classroom.
Keywords: Traductores - Formación profesional; Aptitud; Professional competences; Translator training; Prospective translators; Translators’ concerns